MODEL DAN STRATEGI PEMBELAJARAN QUANTUM TEACHING & LEARNING - Khusnul Khotimah Nasution (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
This research presents an exploration of the Quantum Teaching & Learning model and its associated strategies. Quantum Teaching & Learning is an innovative approach to education that blends various pedagogical methods, technology integration, and learner-centric practices. This study delves into the key components and principles of the model, emphasizing its adaptability to diverse educational settings and subjects. The research also investigates the effectiveness of Quantum Teaching & Learning in enhancing student engagement, critical thinking, and overall learning outcomes. Additionally, it discusses the challenges and opportunities for implementing this model in contemporary educational contexts.